2022
DOI: 10.1038/s41598-022-06025-w
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of AAV-delivered CRISPR/Cas9-based degradation of the HPV18-E6 gene in HeLa cells

Abstract: Human papillomavirus infections are associated with most cervical cancers, which are the fourth most common cancer in women. HPV-E6 protein binds to protein p53 and inhibits its function, leading to the switching of normal cells toward cancer cells. Here, we disrupted the HPV-E6 gene and investigated its effects on the proliferation and apoptosis of HeLa cells. The HPV18-E6 gene was targeted with two designed sgRNAs cloned into an AAV-CRISPR-based plasmid. The AAV-E6-CRISPR/Cas9 virions were prepared and titra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(28 reference statements)
0
5
0
Order By: Relevance
“… 379 Studies have shown that knocking out the E6 and E7 oncogenes using the CRISPR/Cas system can inhibit tumor growth. Targeting the E6 oncogene leads to reactivation of the p53 tumor suppressor pathway, 380 while targeting the E7 oncogene results in the restoration of Rb tumor suppressor pathway. 381 Moreover, recent studies have demonstrated that CRISPR can directly hyperactivate p53 and eliminate HPV‐driven cervical cancer cells.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“… 379 Studies have shown that knocking out the E6 and E7 oncogenes using the CRISPR/Cas system can inhibit tumor growth. Targeting the E6 oncogene leads to reactivation of the p53 tumor suppressor pathway, 380 while targeting the E7 oncogene results in the restoration of Rb tumor suppressor pathway. 381 Moreover, recent studies have demonstrated that CRISPR can directly hyperactivate p53 and eliminate HPV‐driven cervical cancer cells.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…As an HR-HPV, HPV-18 has been targeted and tested in vitro and in vivo . Previous studies showed that oncogenes E6 and E7 of HPV18 could be successfully inhibited by the CRISPR-Cas9 system ( 39 , 40 , 57 , 58 ). However, HPV-6/11, which are low-risk HPV types most common in anogenital warts and laryngeal papillomatosis, also encode the oncoproteins E6/E7.…”
Section: Application Of Crispr-cas9 In Hpv Cancer Therapymentioning
confidence: 99%
“…Additionally, AAV can have stable transgene expression with long-term existence as a concatemer in nondividing cells ( 93 ). The AAV-based CRISPR-Cas9 machine has been used for disruption of the E6 gene in HeLa, which emphasized AAV-based viral vectors as one of the most sensitive viral vectors for gene remedy and gene switch in vivo ( 40 , 58 ).…”
Section: Application Of Crispr-cas9 In Hpv Cancer Therapymentioning
confidence: 99%
“…CRISPR/Cas9 system has shown encouraging results in cervical cancer targeted therapy. However, many obstacles involving off-target effects, immunogenic reactions, renal elimination, degradation of the guide RNA (gRNA) nuclease, delivery, and transportation system limited the application of this robust technology ( Aghamiri et al., 2020 ; Noroozi et al., 2022 ). Therefore, further validation of this technology is required to ensure safety and feasibility ( Zhen and Li, 2017 ).…”
Section: Applications Of Crispr/cas Technology In Targeting Viral And...mentioning
confidence: 99%